Road safety survey 2001 - Swedish Road Administration (University1, 2014)
This is the 21th study in a series of annual surveys on road safety conducted since 1981. The study is conducted by Statistics Sweden on behalf of the Swedish National Road Administration, which had the overall responsibility for road safety in Sweden in 2001. Today the study is conducted on behalf of the Swedish Transport Administration.

The study aims to identify and analyse traffic safety statistics. This is done by a written questionnaire directed to a stratified sample of the population. The study from 2001 had a 70,8 percent response rate and a sample of 10 308 randomly selected people aged between 15 and 84 years.

The questions in the study include, for example, traffic behaviour and traffic patterns; attitudes to road safety and traffic rules, the relation between alcohol and traffic and child safety in traffic. Both motor traffic, bicycle and foot traffic is concerned. A total of 25 questions are used, including descriptive questions, estimation questions and attitude questions.

Purpose:

The survey aims to identify and analyse traffic safety statistics.

Detta är den tjugoförsta studien i en serie av årliga undersökningar om trafiksäkerhet, som genomförts sedan 1981. Studien har genomförts av Statistiska centralbyrån på uppdrag av Vägverket, som 2001 hade det övergripande ansvaret för trafiksäkerheten i Sverige. Idag utförs studien på uppdrag av Trafikverket.

Undersökningen syftar till att ta fram och analysera trafiksäkerhetsstatistik. Detta görs med en skriftlig enkät riktad till ett stratifierat urval av Sveriges befolkning. För studien 2001 var svarsfrekvensen 70,80 procent och urvalet 10 308 slumpmässigt utvalda personer i åldrarna 15 till 84 år.

Frågorna i studien behandlar bland annat trafikbeteende och trafikvanor, både hos sig själv och andra, inställning till trafiksäkerhet och trafikregler, relationen mellan alkohol och trafik samt barns säkerhet i trafiken. Både motortrafik, cykel och gångtrafik berörs. Totalt används 25 stycken frågor som består bland annat av beskrivande frågor, skattningsfrågor och attitydfrågor.

Syfte:

Syftet med studien är att ta fram och analysera trafiksäkerhetsstatistik.
Trafiksäkerhetsenkäten 2001
TS-enkäten 2001
Keywords: drinking behaviour; alkoholvanor; cars; bilar; road traffic; vägtrafik; speed limits; fartgräns; road accidents; trafikolyckor; cyclists; cyklister; child safety; barnsäkerhet; traffic regulations; trafikbestämmelse; bicycles; cyklar; traffic; trafik; cycle lanes; cykelbanor; road users; vägtrafikanter; velocity; hastighet; vehicle restraint systems; bilens inre säkerhet; traffic offences; trafikförseelse; Legislation and legal systems; Lagstiftning och rättssystem; Children; Barn; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap